(untitled) (Fiep Bulletin - online, 2011)
Adventure sports developed normally in the wild, scuba diving, an adventure activity, is the individual’s immersion in liquid without communication with the surface, this activity is considered an adventure in harmony with nature, where it is perceived a greater concern for the pleasure of being close to nature. Cunha observes human intervention as factors affecting the nature and quality of water, the release of domestic and industrial effluents; interference in the flow of sediments and hydrodynamics, due to dredging and landfill and construction of jetties, wharfs and all sorts of foreign elements on the water surface, marginal areas and mangroves; deviations courses channels, and the construction of protective dikes and canals. We performed a literature review to determine the health conditions acceptable to the individual’s immersion in water, and search through longitudinal survey with an open question proposed for divers to determine which factors most influence on the water the decision to be scuba dive. We reported by all 47 interviewees that the transparency of the water its color and light reflection are crucial for choosing the development of this activity. Also, they reported that the conditions occurring in the access to water, such as the infrastructure of vessels or piers or even the sea conditions and access to beaches, determined the choice of the places where the dumping would occur. To take place as part of a process of sustainable social development through tourism, it is necessary to control the quality and transparency of water to immersion and care infrastructure to access it.